2014
DOI: 10.1051/e3sconf/20140301010
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Heat Transfer in Terraced Houses of Tropical Climate

Abstract: Heat is the process of energy circulation and replacement of air from hot to cold. In tropical climates, more heat is received because of the location of Malaysia of the equatorial line. Excessive heat in buildings causes discomfort to the occupants in tropical climate. Tropical rainforest climate receives higher solar radiation and terrestrial radiation reaching the building envelopes contributes to this problem. The design of the building should be more concern on reducing this heat. This paper provides a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The Uniform Building By-Law 1984 (UBBL 1984) states that a terraced house could be referred to as any residential building that is designed as a single dwelling unit, and forms part of a terrace of not less than three such residential buildings [29]. Terraced houses usually have a narrow frontage, and the party walls are shared with adjacent houses [30]. Internal partition walls within the narrow terrace housing layout define living spaces, such as living room, bedrooms, utility, bathroom, and kitchen.…”
Section: Literature Review 21 Terraced Houses With Air-well Systemsmentioning
confidence: 99%
“…The Uniform Building By-Law 1984 (UBBL 1984) states that a terraced house could be referred to as any residential building that is designed as a single dwelling unit, and forms part of a terrace of not less than three such residential buildings [29]. Terraced houses usually have a narrow frontage, and the party walls are shared with adjacent houses [30]. Internal partition walls within the narrow terrace housing layout define living spaces, such as living room, bedrooms, utility, bathroom, and kitchen.…”
Section: Literature Review 21 Terraced Houses With Air-well Systemsmentioning
confidence: 99%
“…In addition, Sadafi et al [7] highlighted through their research, most of local terraced houses do not fulfil the requirements as thermally comfortable indoor environment. Ubiquitously, it is observed that terraced houses are mainly built with reinforced concrete structure with cement plastered clay or cement brick wall panels and roofed with cement roof tiles on timber or galvanised iron structure [8,9]. The doors and windows are not sealed and the orientation of houses are not according to the direction of the sun but the design of long streets and maximisation of housing density per acre to maximise profit.…”
Section: Terraced Housesmentioning
confidence: 99%
“…Due to its location in the tropical climate region, terrace houses in Malaysia usually experienced warmer indoor conditions caused by solar radiation 2 . Azzmi and Jamaludin 3 mentioned that solar radiation is the most significant input of the indoor heat, in which solar radiation absorbed by materials on the building façade gains energy and brings warmth into the building through conduction. According to Kuppusamy, 4 the heat from solar radiation stored in the concrete mass of Malaysian houses during the daytime increases the indoor temperature by 2–5°C higher than the outdoor temperature, which eventually could cause thermal discomfort to the occupants.…”
Section: Introductionmentioning
confidence: 99%